Spiritual Resilience: Content And Criteria, Opportunities for Strengthening (Zien Journal of Social Sciences and Humanities, 2025)
Spiritual resilience is the capacity to maintain a positive spirit and overcome obstacles through a deep sense of purpose and connection with the broader aspects of life. This article explores the content and criteria of spiritual resilience and identifies opportunities for its strengthening. Through an interdisciplinary approach combining psychology, theology, and sociology, we examine the methods employed to enhance spiritual resilience and provide practical applications that can be integrated into daily life. The insights provided aim to foster a deeper understanding and appreciation of spiritual resilience as an integral aspect of human flourishing.